2020
DOI: 10.1111/aab.12661
|View full text |Cite
|
Sign up to set email alerts
|

Augmented descriptions of growth and development stages of potato (Solanum tuberosum L.) grown from different types of planting material

Abstract: The recent invention of hybrid breeding technology for potato has led to an increased interest in hybrid potato R&D. Hybrid true potato seeds (TPS) are used to produce planting materials such as transplants and seedling tubers, but can also be used for direct seeding of seed or ware crops. Transplants and seedling tubers can be used to produce seed tubers or ware tubers. The rise in R&D in hybrid breeding creates the need for phenological scales of growth and development of plants produced by the various plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 22 publications
0
30
0
1
Order By: Relevance
“…It is suggested that more cultivar-specific trials are conducted when improved hybrid potato cultivars become available to growers. These studies will contribute with the current study, and those carried out by Kacheyo et al (2021), Stockem et al (2020) and van Dijk et al (2021), useful information on the novel cultivation systems for hybrid potato, including crop management recommendations. More information will also be required on the optimal field conditions at the moment of transplanting and the subsequent seedling establishing period to enhance quick plant development.…”
Section: Further Studiesmentioning
confidence: 85%
See 2 more Smart Citations
“…It is suggested that more cultivar-specific trials are conducted when improved hybrid potato cultivars become available to growers. These studies will contribute with the current study, and those carried out by Kacheyo et al (2021), Stockem et al (2020) and van Dijk et al (2021), useful information on the novel cultivation systems for hybrid potato, including crop management recommendations. More information will also be required on the optimal field conditions at the moment of transplanting and the subsequent seedling establishing period to enhance quick plant development.…”
Section: Further Studiesmentioning
confidence: 85%
“…Hybrid true seeds were sown by hand in 104-plug nursery trays on 13 April in 2017 and on 3 April in 2018 and cultivated as described by van Dijk et al (2021). Five weeks after sowing, 1 day prior to transplanting, a selection of transplantable seedlings (measuring 7-12 cm above-ground, containing 5-8 true leaves, BBCH stage 105-108; Kacheyo et al 2021) was made consistent with the protocol of van , after which seedlings were irrigated and loaded for transport to the field locations.…”
Section: Hybrid Potato Genotypes and Greenhouse Nurserymentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in tuber traits within one plant can be the result of environmental conditions during the growing season (Struik et al 1991). Moreover, stolon characteristics and timing of stolon and tuber formation can result in variation in tuber characteristics (Struik et al 1991;Van Ittersum and Struik 1992;Kacheyo et al 2021). The variation of the tuber traits was more difficult to estimate than the tuber traits themselves: the plot size and LSD% on the point of maximum curvature were higher for the models of SD of tuber volume and shape than for tuber volume and shape themselves.…”
Section: Optimal Plot Size Differs For Different Traitsmentioning
confidence: 99%
“…Snoek et al 1985;Timmer et al 1989;Neuvel et al 1991), for which potato is sensitive (Hijmans et al 2003;Bethke et al 2019). Large, over-developed transplants (BBCH stage 109 and further, Kacheyo et al 2021) are also associated with high risk of mechanical damage during transplanting, and with increased transpiration rates (Reekie et al 2005(Reekie et al , 2007 which can cause wilting of the seedling (Snoek et al 1985). On the other hand, transplanting of small, under-developed seedlings (BBCH stage < 102, Kacheyo et al 2021) in open field conditions leads to delayed establishment and growth of seedlings, which negatively impacts the length of the crop growth cycle (Everaarts et al 1993;Kerbiriou et al 2013).…”
Section: Introductionmentioning
confidence: 99%